Student perceptions in learning accounting through open distance learning (odl): a case study of UiTM Pahang students - M Yacob, Noor Hasimah; Mohammad Fadzillah, Nur Syazwani; Wan Abdul Rahman, Nor Hawani; Mustafa, Lily Mazlifa; Jamaluddin, Sabariah; Mat Bahari, Anis Barieyah (GADING Journal for the Social Sciences, 2023)
Open distance learning (ODL) is the best alternative to ensure the continuation of the teaching and learning process during the pandemic SARS-CoV-2 virus (COVID-19). However, not all courses offered by universities are suitable to be studied using ODL, especially courses that involve calculations and applications of formulae. Due to this issue, students’ experience in learning this type of course needs to be examined further. This study is necessary to ensure that the teaching and learning process using ODL mode can be carried out smoothly and successfully. Therefore, this paper aims to study the perception of students in learning accounting courses through ODL mode. Besides that, this study also intends to investigate the differences in the student’s perception of learning accounting through ODL based on their gender and seniority level. In achieving the objectives of the study, the data was gathered from a set of questionnaires distributed to students under going accounting courses in UiTM Pahang, Jengka Branch through an online platform. The results show that most of the students did not prefer learning accounting through ODL. Meanwhile, there were no significant differences between males and females in terms of students’ perceptions of learning accounting through ODL. However, seniority level was found to have an effect on the student’s perceptions of accounting and ODL. The result of the study might be used by respective authorities to improve the guidelines on the ODL process in the future. Further study should be conducted to investigate the impact of ODL on the quality of graduates in the university.